Impact of Age, Sex and Route of Administration on Adverse Events after Opioid Treatment in the Emergency Department: A Retrospective Study - Raoul Daoust; Jean Paquet; Gilles Lavigne; Éric Piette; Jean-Marc Chauny (Pain Research and Management)
BACKGROUND: The efficacy of opioids for acute pain relief in the emergency department (ED) is well recognized, but treatment with opioids is associated with adverse events ranging from minor discomforts to life-threatening events.